2005
DOI: 10.1097/01.ju.0000169475.00949.78
|View full text |Cite
|
Sign up to set email alerts
|

Do Margins Matter? The Prognostic Significance of Positive Surgical Margins in Radical Prostatectomy Specimens

Abstract: We confirm that a PSM has a significant adverse impact on PFP after RP in multivariate analysis using multiple statistical methods to account for patients who received AT. While prostate cancer screening strategies have resulted in a majority of men having organ confined disease at RP, surgeons should continue to strive to reduce the rate of positive surgical margins to improve cancer control outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
207
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(228 citation statements)
references
References 20 publications
15
207
3
3
Order By: Relevance
“…Although the extent of the PSM has been shown to be associated with BCR after RP, few reports have shown its significance in relation to clinical outcomes or PC-specific mortality [2,4]. Furthermore, several studies have demonstrated that PSM is an independent predictor of BCR [3,18]. However, BCR is not a universally accepted surrogate endpoint for clinical failure or PC-specific mortality [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the extent of the PSM has been shown to be associated with BCR after RP, few reports have shown its significance in relation to clinical outcomes or PC-specific mortality [2,4]. Furthermore, several studies have demonstrated that PSM is an independent predictor of BCR [3,18]. However, BCR is not a universally accepted surrogate endpoint for clinical failure or PC-specific mortality [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…BCR after RP has been associated with multiple factors, including the preoperative PSA level, the pathological stage, the GS of the prostatectomy specimen, and the surgical margin status [2,3,4,7,16,17]. Although the extent of the PSM has been shown to be associated with BCR after RP, few reports have shown its significance in relation to clinical outcomes or PC-specific mortality [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the radical prostatectomy (RP), as also that of the robot-assisted laparoscopic radical prostatectomy (RARP) is to remove the entire cancer and to strive for clear surgical margins. Positive surgical margins (PSMs) remain a real risk and result in an increased risk for biochemical recurrence (BCR) and a decrease in disease-free survival [1,2], especially in organ-confined disease [3]. PSMs in organ-confined PCa are iatrogenic [1] and are the only poor prognostic factor influenced by the surgeon [4].…”
Section: Introductionmentioning
confidence: 99%
“…Positive surgical margins (PSMs) remain a real risk and result in an increased risk for biochemical recurrence (BCR) and a decrease in disease-free survival [1,2], especially in organ-confined disease [3]. PSMs in organ-confined PCa are iatrogenic [1] and are the only poor prognostic factor influenced by the surgeon [4]. In addition, it has been postulated that the nerve-sparing approach could also increase the PSM rate.…”
Section: Introductionmentioning
confidence: 99%